THE EFFECT OF PROFITABILITY AND LEVERAGE ON FIRM VALUE WITH INSTITUTIONAL OWNERSHIP AS A MODERATING VARIABLE IN CONSUMER NON-CYCLICAL FIRMS - Kholid Ubaedillah; Erwin Budianto; Agustina Budianto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This study aims to measure the impact of profitability and leverage on firm value, with institutional ownership serving as a moderator variable. Focusing on companies in the Non-Cyclical Consumer Goods sector listed on the Indonesia Stock Exchange from 2022 to 2024, this study employs a quantitative associative approach and uses secondary financial data. Through purposive sampling, this study analyzes 36 firm-year observations using SPSS 25 via multiple linear regression and moderated regression analysis. Empirical findings indicate that profitability (ROA) positively and significantly influences firm value (Tobin’s Q). Similarly, leverage (DER) exerts a positive and significant effect on firm value in the baseline model. Moderation analysis reveals that institutional ownership strengthens the relationship between profitability and firm value, but does not significantly moderate the effect of leverage. The uniqueness of this study lies in its focus on the Non-Cyclical Consumer Goods sector amid recent economic changes. These results suggest that future research should incorporate additional corporate governance indicators and cross-industry comparisons to better identify the drivers of firm value.